The Prevalence of Symptomatic Dermographism: Results of the International UCARE PREVALENCE-D Study - Kulthanan, Kanokvalai; Bernstein, Jonathan A; Rudenko, Michael; Salameh, Pascale; Komoltri, Chulaluk; Adışen, Esra; Al Abri, Salma; Al-Ahmad, Mona; Al-Ahmed, Nasser; Al Hinai, Bushra; Allenova, Anastasiia; Alshareef, Saad; et al. (Wiley, 2025)
The prevalence of symptomatic dermographism (SD) in the general population remains unclear. This study aimed to internationally estimate the prevalence of SD and two other dermographic subtypes-physiological red dermographism and simple urticarial dermographism-among adults worldwide.